A supply chain practice-based view of enablers, inhibitors and benefits for environmental supply chain performance measurement. Issue 5 (4th April 2021) - Shaw, Sarah; Grant, David B.; Mangan, John
Abstract: Organisations face ever increasing pressure to deliver triple-bottom-line performance results in their supply chains. Yet despite the importance and complexity associated with environmental supply chain performance measurement (ESCPM), organisations struggle to achieve this. The purpose of this paper is to identify the important enablers, inhibitors and benefits to implementing ESCPM as a practice in firms. Data were collected from three focus groups and an industry survey of 388 UK supply chain professionals in a three-phase empirical study. Eighteen enablers, seventeen inhibitors and eleven benefits were identified and ranked in importance. A supply chain practice-based view was utilised as an overarching theoretical lens to conceptualise the study's findings and propose nineteen antecedents, arranged in a hierarchical framework, to enable practitioners to make effective ESCPM decisions. This paper provides an up-to-date review of the factors which influence ESCPM practice, addressing the need for additional research in this area.